Assessment of secular trends of three major gynecologic cancers burden and attributable risk factors from 1990 to 2019: an age period cohort analysis - Yiran Liu; Wenqi Shi; Sumaira Mubarik; Fang Wang (BMC, 2024)
Abstract Background This study aims to assess the long-term trends in the burden of three major gynecologic cancers(GCs) stratified by social-demographic status across the world from 1990 to 2019. To assess the trends of risk factor attributed mortality, and to examine the specific effects of age, period, cohort behind them in different regions. Methods We extracted data on the mortality, disability-adjusted life years(DALYs), and age-standardized rates(ASRs) of cervical cancer(CC), uterine cancer(UC), and ovarian cancer(OC) related to risks from 1990 to 2019, as GCs burden measures. Age-period-cohort analysis was used to analyze trends in attributable mortality rates. Results The number of deaths and DALYs for CC, UC and OC increased since 1990 worldwide, while the ASDRs decreased. Regionally, the ASDR of CC was the highest in low SDI region at 15.05(11.92, 18.46) per 100,000 in 2019, while the ASDRs of UC and OC were highest in high SDI region at 2.52(2.32,2.64), and 5.67(5.16,6.09). The risk of CC death caused by unsafe sex increased with age and then gradually stabilized, with regional differences. The period effect of CC death attributed to smoking showed a downward trend. The cohort effect of UC death attributed to high BMI decreased in each region, especially in the early period in middle, low-middle and low SDI areas. Conclusions Global secular trends of attributed mortality for the three GCs and their age, period, and cohort effects may reflect the diagnosis and treatment progress, rapid socioeconomic transitions, concomitant changes in lifestyle and behavioral patterns in different developing regions. Prevention and controllable measures should be carried out according to the epidemic status in different countries, raising awareness of risk factors to reduce future burden.